“Commitment to collaboration”: What students have to say about the values underpinning partnership practices - Luo, Benjamin; Matthews, Kelly; Chunduri, Prasad (International Journal for Students as Partners, 2019)
Students as Partners (SaP) is about students and staff working together in teaching and learning. It is guided by the values of partnership. Knowing how students understand these values, particularly students new to the ideas and language of SaP, would enrich the scholarly conversation about partnership practices. To that end, our study asked students unfamiliar with SaP, “what values and attitudes do you think are necessary for students and academics to work as collaborative partners on teaching and learning?” We captured 173 written responses from students in a biomedical sciences degree program in an Australian university. Thematic analysis revealed four key values: respect, communication, understanding, and responsibility/commitment. We discuss the results through the lens of reciprocity and power, emergent consumerist culture in higher education, and the disciplinary context of science. In conclusion, we encourage dialogue between staff and students to illuminate and affirm the values of partnership that define SaP.